Pengembangan Model Pembelajaran Collaborative Problem Based Learning Pada Pembelajaran Kimia di Perguruan Tinggi - Rusly Hidayah; Fauziatul Fajaroh; Romita Erika Narestifuri (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
Learning activities, especially in chemistry lessons, are challenging and quite complicated learning activities. In addition, the provision of information such as teaching materials from lecturers needs to be reduced so that students can find, process, and use the learning resources they get. One of the learning models that can be used is the Collaborative Learning (CL) and Problem Based Learning (PBL) models. This model provides an opportunity to develop the social skills needed. Therefore, the researcher took the initiative to conduct a literature study to determine the effect of applying CL and PBL on chemistry learning. This research was conducted using a systematic analysis approach through several references in the form of journals published in the last 10 years, articles relevant to the research topic. Based on research results from several journals, it can be concluded that the CL model combined with PBL allows lecturers and students to share information more effectively and efficiently.